POSTCOLONIAL TRANSNATIONAL DISPLACEMENT AND THE RECONSTRUCTION OF IDENTITY IN EXIT WEST AND BY THE SEA (Contemporary Journal of Social Science Review, 2025)
This study explores the complex dynamics of transnational displacement and identity reconstruction in Mohsin Hamid’s Exit West and Abdulrazak Gurnah’s By the Sea, situating both novels within a postcolonial framework. Through a comparative analysis, it examines how forced migration acts as both a physical and psychological rupture, reshaping individual identities amid cultural dissonance, trauma, and the legacies of colonialism. Hamid’s use of magical realism dismantles traditional notions of borders and nationhood, presenting migration as a fluid and transformative experience, while Gurnah’s realist narrative foregrounds the silenced voices of refugees and asylum seekers navigating postcolonial power structures. Drawing on postcolonial theorists such as Homi Bhabha, Edward Said, and Gayatri Spivak, the study reveals how these texts challenge dominant discourses on migration by portraying the multifaceted processes of identity negotiation, hybridity, and belonging. Ultimately, this paper highlights the vital role of literature in humanizing refugee experiences and advancing scholarly conversations about displacement and identity in the contemporary postcolonial world.